Serum Bilirubin as a Potential Marker in Diagnosing the Severity of Acute Appendicitis: A Retrospective Study - Shrestha, Sanjay Bikram; Thakur, Jay Prakash; Pradhan, Manisha; Jha, Rupa; Tamang, Shanti (Journal of College of Medical Sciences-Nepal, 2025)
Background Acute appendicitis ranks among the leading causes of emergency abdominal surgeries. Although clinical assessments and imaging techniques are crucial for diagnosis, a straightforward and economical biomarker to evaluate severity is yet to be identified. Recent research indicates that serum bilirubin might act as a surrogate indicator of disease severity. The objective of this study was to analyse the relationship between serum bilirubin concentrations and the severity of acute appendicitis. Methods A retrospective case-control study was performed on patients who underwent appendectomy at Green City Hospital from June 1, 2023 to May 31, 2025. Patients with chronic liver disease, haemolytic disorders, conditions that influence bilirubin metabolism, or those with alternative diagnoses post-surgery were excluded. Patients were classified into normal (≤1 mg/dL) and elevated (>1 mg/dL) groups based on serum bilirubin levels. Intraoperative findings of the appendix were categorized as normal, inflamed, or complicated (gangrenous, perforated). Pearson’s correlation coefficient was utilized to evaluate the correlation between bilirubin levels and the severity of appendicitis. Results Among the 170 patients screened, 156 were included in the analysis. Four patients had normal appendices, and all had normal bilirubin levels. Out of 127 patients with inflamed appendices, 123(96.85%) exhibited normal bilirubin. Of the 25 patients with complicated appendicitis, 17(68%) had elevated bilirubin levels. A strong positive correlation (r=0.650, p-value<0.000) was established between bilirubin concentrations and disease severity. Conclusions Increased serum bilirubin levels demonstrate a significant association with the severity of acute appendicitis and may be a valuable additional marker in clinical assessments.